Peran Guru dalam Optimalisasi Papan Interaktif Digital pada Pembelajaran Pengolahan Data di SD Negeri 1 Karangmloko - Utami, Linda Tri; Muhammad, Azamul Fadhly Noor (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to describe the teacher's role in optimizing the use of Digital Interactive Boards (DIB) in teaching data processing topics in fifth-grade mathematics at SD Negeri Karangmloko 1. The integration of digital technology in mathematics is considered an effective strategy to improve learning quality by presenting concepts in a more visual, interactive, and meaningful manner. This study employed a qualitative approach with a descriptive research design. The participants consisted of a fifth-grade teacher and fifth-grade students of SD Negeri Karangmloko 1. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that teachers played a crucial role throughout the learning process, including planning, implementation, and evaluation stages. During the planning stage, teachers prepared instructional materials, designed digital learning media, and developed visual representations of data processing concepts. In the implementation stage, teachers acted as facilitators by guiding students to actively engage with the Digital Interactive Board. During evaluation, teachers utilized interactive quiz features to assess students’ understanding and provide immediate feedback. The use of DIB enhanced students’ attention, motivation, participation, and comprehension of data processing materials. Therefore, the successful integration of Digital Interactive Boards in mathematics learning is highly dependent on teachers’ ability to design, manage, and evaluate technology-based instruction effectively.